Menakar Sejarah Memaknai Kehidupan: Kajian Psikohistoris Teologi Jemaat GPM Hatuhenu Tahun 1950-1953 - Fiktor Fadirsair (Program Pascasarjana UKIM, 2023)
Revealing history is the essence of life that is based on human reality in the past by looking at how humans act, think, feel, and do things. The events that have occurred in the past, affect the psychological reality of society both individually and collectively towards the political, social, cultural, and economic dimensions. This article aims to measure the history of the people in the GPM Hatuhenu Congregation, Masohi Clasis who had to move to avoid conflict and find the right place to settle. The displacement that occurred due to the upheaval of the RMS in 1950, was against the propaganda carried out with the aim of maintaining Christianity. With a psycho-historical approach, the author finds theological meaning that in the midst of a history of destruction, and the threat of death, there is a work of God who suffers and liberates so that the people in the GPM Hatuhenu congregation escape the habit, and survive in the midst of challenges to build the future.